Assessment of family psychosocial functioning in survivors of pediatric cancer using the PAT2.0. Issue 9 (26th March 2013) - Gilleland, Jordan; Reed‐Knight, Bonney; Brand, Sarah; Griffin, Anya; Wasilewski‐Masker, Karen; Meacham, Lillian; Mertens, Ann
Abstract: Background: This study aimed to examine clinical validity and utility of a screening measure for familial psychosocial risk, the Psychosocial Assessment Tool 2.0 (PAT2.0), among pediatric cancer survivors participating in long‐term survivorship care. Methods: Caregivers ( N = 79) completed the PAT2.0 during their child's survivorship appointment. Caregivers also reported on family engagement in outpatient mental health treatment. Medical records were reviewed for treatment history and oncology provider initiated psychology consults. Results: The internal consistency of the PAT2.0 total score in this survivorship sample was strong. Psychology was consulted by the oncology provider to see 53% of participant families, and families seen by psychology had significantly higher PAT2.0 total scores than families without psychology consults. PAT2.0 total scores and corresponding subscales were higher for patients, parents, and siblings enrolled in outpatient mental health services since treatment completion. Results were consistent with psychosocial risk categories presented within the Pediatric Psychosocial Preventative Health Model. Fifty‐one percent of families presenting for survivorship care scored in the "universal" category, 34% scored in the "targeted" category, and 15% scored in the "clinical" category. Conclusions: Data indicate that the overall proportions of families experiencing "universal", "targeted", and "clinical" levels of familial distress may be constant from the time of diagnosis into survivorship care. Overall, the PAT2.0 demonstrated strong psychometric properties among survivors of pediatric cancer and shows promise as a psychosocial screening measure to facilitate more effective family support in survivorship care. Copyright © 2013 John Wiley & Sons, Ltd.